On Development of Meir-Keeler Type Fixed Point Theorems - Jha, K.; Rao, K. P.R.; Panthi, D. (Nepal Journal of Science and Technology, 2010)
The theory of fixed point is a very extensive field, which has various applications. The present paper deals with some developments of Meir-Keeler type fixed point theorem as its remarkable generalizations under several contractive definitions in metric space. Key words: Common fixed point; Contraction; Metric space; Compatible maps DOI: 10.3126/njst.v10i0.2956 Nepal Journal of Science and Technology Vol. 10, 2009 Page: 141-147